Interactions Between Knowledge and Testimony in Children's Reality-Status Judgments. Issue 3 (26th May 2016) - Lopez-Mobilia, Gabriel; Woolley, Jacqueline D.
Abstract : In 2 studies, we attempted to capture the information-processing abilities underlying children's reality-status judgments. Forty 5- to 6-year-olds and 53 7- to 8-year-olds heard about novel entities (animals) that varied in their fit with children's world knowledge. After hearing about each entity, children could either guess reality status immediately or listen to testimony first. Informants varied in their expertise and in their testimony, which either supported or refuted the entities' existence. Results revealed that children were able to evaluate the fit between the new information and their existing knowledge; this information then governed their decision regarding whether to seek testimony. Testimony had the strongest effect when new information did not conflict with, but was also not representative of, children's knowledge.